Determining standard grades for the level of cognitive achievement in some basic skills of karate for juniors 12/10 years - Bouchouareb, abdelbasset; bechir , houssem (sports creativity, 2025)
The study aims to define standard grades for the level of cognitive achievement in some of the basic skills of karate sport among juniors 10-12 years, through building a cognitive achievement scale for these skills and applying it to the research sample, the researcher used the descriptive approach by the survey method, and the research sample was chosen by the intentional method From the amateur karate sports club for the children of the state of Umm Al-Bouaghi campaign, which consisted of 80 players, and the researcher used questionnaires addressed to many experts in addition to the personal interview, and the study reached building a test consisting of 66 words capable of detecting the level of cognitive